Liberia : Fourth Review of Performance Under the Staff; Monitored Program and Request for Three; Year Arrangement Under the Poverty Reduction and Growth Facility and the Extended Fund Facility; Staff Report; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2008)
This paper reviews Liberia's performance under the staff-monitored program (SMP) through December 2007, and proposes a three-year program to be supported by the Poverty Reduction and Growth Facility (PRGF) and the Extended Fund Facility (EFF) once Liberia's arrears to the IMF have been cleared and its rights to access IMF resources restored. Satisfactory performance on the PRGF/EFF-supported program would pave the way for comprehensive treatment of external debt under the Heavily Indebted Poor Countries (HIPC) Initiative and beyond-HIPC debt relief.